The rock from the sky - Klassen, Jon (Candlewick Press, 2021)
The Caldecott Medal-winning creator of the Hat trilogy presents a hilariously deadpan meditation on the workings of friendship, fate, foresight and the funny feeling that something is off, when two companions stand in a perfectly good spot that may be hit, sometime, by a falling rock.